Disseminated histoplasmosis: a rare clinical phenotype with difficult diagnosis. Issue 3 (26th February 2017) - Xiong, Xiao‐feng; Fan, Li‐li; Kang, Mei; Wei, Jia; Cheng, De‐yun
Abstract : We describe a rare and interesting case of a 37‐year‐old man who presented with an intermittent fever, progressive cytopenia, and hepatosplenomegaly. Histopathological examination of a bone marrow smear revealed haemophagocytes and intracellular yeast‐like Histoplasma capsulatum ( H. capsulatum ); thus, we prolonged the blood culture duration to detect fungi, and H. capsulatum was detected in the peripheral blood. After the diagnosis of disseminated histoplasmosis, the patient was successfully treated with amphotericin B and symptomatic therapy. This is the first case in southwest China for which H. capsulatum was cultivated in peripheral blood, illustrating that the duration of specimen culture should be lengthened if a specific pathogen infection is suspected. Moreover, this case enriches our understanding of clinical manifestations of disseminated histoplasmosis. Abstract : We present a rare and interesting case of disseminated histoplasmosis in a patient without AIDS. To the best of our knowledge, this is the first case in which Histoplasma capsulatum was cultivated in blood in southwest China.